WHERE THE WIND BLOWS - Maden, Mike; Schimke, John; Donovan, Trevor, 1978-; Elaine, Ashley; Howell, C. Thomas, 1966-; Hurd, Michelle; Fyffe, Caroline (Level 33 Entertainment, 2025)
Based on the acclaimed novel by best-selling author Caroline Fyffe. A hardened cowboy puts his unfettered life on the open range on pause when he pretends to be a temporary husband for his late friend's widow so she can adopt. The two go from strangers to something neither expected: a chance at love.